The effects of agricultural policy on supply and productivity: Evidence from differential changes in distortions. (16th September 2022) - Hendricks, Nathan P.; Smith, Aaron; Villoria, Nelson B.; Stigler, Matthieu
Abstract: Incentives in agriculture are highly distorted. It has long been argued that these distortions were a key explanation for differences in supply and productivity across countries, but the empirical evidence is limited. We revisit this issue using data on policy distortions across 63 countries for the period 1961–2011. We estimate the effects of differential changes in agricultural distortions across countries on supply and productivity. We highlight concerns in our analysis and previous work about endogeneity that biases the estimated effect downward—countries that lose comparative advantage are likely to increase support for agriculture. We address these concerns by including country and region‐time fixed effects, along with a rich set of controls. Overall, we find evidence that enhanced incentives through policy changes can increase the rate of production growth, with about half of the increase due to productivity increases. This result is strongest in Sub‐Saharan Africa where anti‐agricultural policies on exports were reduced and in Europe where pro‐agricultural policies on imports were reduced, driven largely by external pressure. Endogeneity appears to be strongest in Asia where countries have followed the typical pattern of raising support for agriculture during industrialization due to a rising farm‐urban income gap.